2021
DOI: 10.1590/fst.01020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of malathion, chlorpyrifos, λ-cyhalothrin and arsenic in rice

Abstract: Presented study focused on the incidence of pesticides: malathion, chlorpyrifos and λ-cyhalothrin and heavy metal, arsenic in the rice samples collected from the three main rice growing areas. 30 samples of brown Super Kernel Basmati rice and Super Basmati rice varieties, irrigated through tube well irrigation were selected. Highly sensitive and selective method of High Performance Liquid Chromatography was used for determination of pesticides. Results of analysis showed the presence of malathion in one sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Our Pakistani group presented the concentration of 0.075 ± 0.05 mg kg −1 presented by Almutairi et al [ 33 ]. Hamid et al [ 47 ] observed a higher chlorpyrifos concentration of 3.3 mg kg −1 and 1.45 mg kg −1 in two Pakistani brown rice samples.…”
Section: Resultsmentioning
confidence: 99%
“…Our Pakistani group presented the concentration of 0.075 ± 0.05 mg kg −1 presented by Almutairi et al [ 33 ]. Hamid et al [ 47 ] observed a higher chlorpyrifos concentration of 3.3 mg kg −1 and 1.45 mg kg −1 in two Pakistani brown rice samples.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorpyrifos metabolites methyl-chlorpyrifos and their metabolites (oxon forms and trichloro pyridinol) are toxic [5]. Children who had chlorpyrifos in their blood had more developmental delays and disorders, deficit disorders and hyperactivity disorders [5], and also the development of autism [6]. The toxic effects of chlorpyrifos and its metabolites on some physiologically important enzymes ATPases, cholinesterases, and peroxidases [7] have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorpyrifos metabolites methyl‐chlorpyrifos and their metabolites (oxon forms and trichloro pyridinol) are toxic [5]. Children who had chlorpyrifos in their blood had more developmental delays and disorders, deficit disorders and hyperactivity disorders [5], and also the development of autism [6].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a number of methods were established for the detection and quantification of pesticides and related biomarkers. Instrumental detection, such as gas chromatography, high-performance liquid chromatography, and capillary electrophoresis [12,13], is proven as an effective means to detect pesticides. Although these instrumental approaches present the merits of high selectivity and excellent repeatability, the limits including expensive equipment, time-consuming process, and complex operation seriously restrict their use for on-site rapid detection [14].…”
Section: Introductionmentioning
confidence: 99%